2022
DOI: 10.1177/11782218221107021
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on Coming Off Opioid Agonist Treatment: A Qualitative Study

Abstract: Aims: Opioid agonist treatment (OAT) programs are life-saving, as they reduce opioid use, overdoses, and criminal activities. Disadvantages reported with long-term OAT include side effects of the medication, especially on cognitive ability and sexual function, which may discourage potential participants. Many of those who participate in OAT have a desire to come off treatment. The aims of this study were to explore patients’ thoughts about coming off OAT and to investigate their perceptions of what support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Opioid use disorder (OUD) is a chronic recurrent illness1 affecting an estimated 26.8 million people, with an increase in prevalence of over 47.3% over the past 20 years worldwide 2. Although opioid agonist treatment (OAT) is intended as a long-term, potentially indefinite treatment for persons with OUD, many persons may have a strong desire to eventually taper off treatment 3. OAT tapering involves a gradual reduction in daily OAT dosing to ultimately reach a state of opioid abstinence 4.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Opioid use disorder (OUD) is a chronic recurrent illness1 affecting an estimated 26.8 million people, with an increase in prevalence of over 47.3% over the past 20 years worldwide 2. Although opioid agonist treatment (OAT) is intended as a long-term, potentially indefinite treatment for persons with OUD, many persons may have a strong desire to eventually taper off treatment 3. OAT tapering involves a gradual reduction in daily OAT dosing to ultimately reach a state of opioid abstinence 4.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies assessing clients’ perspectives on OAT tapers have indicated that many people with OUD have a desire to eventually discontinue their OAT and achieve a state of abstinence from opioids. A qualitative study of 15 participants in Sweden indicated that clients’ perspectives on tapers are dependent on their duration and response to treatment 3. People in the first 2 years of treatment are less likely to consider tapering off OAT as cravings can be reduced or avoided by receiving an appropriate dose of OAT 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Several models have been suggested to facilitate patient engagement, including shared decision making and using patient-reported goals (PRGs). 24 , 25 PRGs may have distinct advantages over traditional, provider-defined treatment goals, as provider-defined goals may oversimplify the complexities of managing care for a patient with OUD and may value aspects of the care differently from their patients. 26 , 27 , 28 However, complicating the issue is the fact that these patient goals likely shift as a patient moves from addiction through to the various stages of recovery.…”
Section: Introductionmentioning
confidence: 99%